Economic Integration in the Mashreq - World Bank (Washington, DC, 2017)
This report reviews the status of Mashreq countries' economic integration with the world, with the Arab world, and within the Mashreq sub-region itself. It examines the drivers of progress to date and barriers to further integration. It focuses on Mashreq countries' participation in integration agreements; integration through trade, labor, and capital flows; and physical infrastructure. The main findings are that Mashreq countries trade more with the European Union (EU) than with other countries in Middle East and North Africa (MENA) or among themselves, but account for a significant share of MENA's trade in services. With the exception of Iraq, a major oil exporter, the Mashreq countries export a relatively large share of manufactured goods-surpassed only by Tunisia and Morocco. Mashreq exports are relatively less concentrated than other MENA countries, with the exception of Tunisia and Morocco. Regional economic integration would be enhanced through better trade facilitation procedures and by better transport infrastructure. Policies relating to further improving the investment climate and private sector development also matter.